Exploration of Barriers and Facilitators to Healthy Eating in UK Truck Drivers - Katharina B. Ruettger; Elizabeth Stamp; James A. King; Stacy A. Clemes (Safety and Health at Work)
Background: The working environment of truck drivers promotes unhealthy lifestyle behaviours including physical inactivity and poor dietary choices. This leads to high levels of chronic diseases and a reduced life expectancy compared to other occupational groups. However, little is known about how drivers in the UK perceive their working environment and how this affects their food choices. This study aimed to gain a better understanding of long-haul (8–10-hour shifts) truck drivers’ needs regarding healthy food choices whilst on the road to better inform future health promotion programmes and policy needs. Methods: Individual semi-structured interviews were conducted, allowing an in-depth exploration of truck drivers’ experiences. The interview guide was grounded within the COM-B model and theoretical domains framework. Audio recordings were anonymised and transcribed verbatim and data analysed using thematic analysis. Results: Ten drivers (8 male) were interviewed with a mean age of 49 years (SD 9.7). Frequently mentioned barriers to healthy eating were limited availability of affordable healthy food options at truck stops, food storage limitations, and limited time for food preparation. Commonly reported facilitators to improve drivers' diet were flexible break times, shorter shifts, secure parking places and/or better-equipped vehicles. Conclusions: Limited availability of healthy food options, high costs, poor facilities within rest areas, long working hours/shifts, and lack of food storage and preparation time, negatively impacts UK truck drivers’ eating behaviours. This study highlights that multi-component interventions targeting the individual, environment and policy, are ultimately needed to improve truck drivers’ working conditions and health.